Orchestration of Regional Government Organization Capacity to Strengthen Public Aspiration-Oriented Development Planning - Franky Djafar; Rifka S. Akibu; Nanda Moputi (Journal La Sociale, 2025)
This study aims to analyze the orchestration capacity of local government agencies in Gorontalo Regency in integrating community aspirations into development planning. The research employed a descriptive qualitative method with data obtained through in-depth interviews, participatory observations, document reviews, and focus group discussions involving officials, community representatives, and local stakeholders. The analysis focused on three main dimensions, namely technical, analytical, and communication capacity. The findings indicate that capacity fragmentation remains the main obstacle, as agencies with strong technical competence often show weaknesses in analytical ability, while those excelling in public communication tend to be weak in technical aspects. On average, only eighteen to twenty percent of community aspirations are accommodated in the regional budget, reflecting the dominance of sectoral programs, limited fiscal space, and weak inter-agency coordination. These challenges are further reinforced by regulatory frameworks that remain top-down, limiting regional flexibility to adapt policies to local needs. Nevertheless, the study identifies strategic opportunities to strengthen orchestration through the utilization of information technology to enhance transparency, accelerate data flows, improve policy integration, and expand public participation. Additional strategies include developing human resource capacity, promoting evidence-based planning, establishing IT-based coordination forums, and introducing regulations that are more adaptive to local contexts. The study concludes that strengthening orchestration should not be seen merely as an administrative process but as a transformative strategy to realize inclusive, responsive, and sustainable regional development governance.